Working hours in dual-earner couples: Does one partner work less when the other works more? - Ragni Hege Kitterød; Marit Rønsen; Ane Seierstad (Statistics Norway, Research Department, 2011)
In spite of increased labour market participation in recent decades, women in Norway still have high part-time rates and seldom work more than their partners. Given that an aging population implies a projected large labour demand in many Western countries, it is important to explore potential labour market reserves among women. Utilising the panel in the Norwegian part of the EU-SILC, we ask whether an increase in the mother's paid hours is associated with an increase or a decrease in the father's hours, or whether there is no relationship between changes in the partners' working hours at all. An increase from parttime to normal full time for the mother is not associated with a change in the father's hours, but an increase from full time to very long hours for the mother corresponds to an increase in the father's hours. A positive association between the parents' paid hours applies first and foremost to parents with school-aged children and to couples where both partners have either long or short education. When the mother has long education and the father has short, an increase in her paid hours is associated with a decrease in his.
Keywords: J21; J22; J23; 330; Dual-earners; gender equality; labour market; working hours